Making Sense of Operational Assistance Fund Management in Early Childhood Education: A Phenomenological Study - Muh Syamrialdi Farkan S; Wa Ode Rayyani (Penerbit Goodwood, 2025)
Purpose: This study aims to understand and uncover the meaning of the lived experience of Early Childhood Education (ECE) managers in administering the Operational Assistance Fund (Bantuan Operasional Penyelenggaraan or BOP) for early childhood education institutions, with particular emphasis on accountability, responsibility, and the underlying values that shape their managerial practices.Methodology: The study employed a qualitative approach with an Interpretative Phenomenological Analysis (IPA) design. Data were collected through in-depth interviews, participant observation, and documentary study involving a single key informant who manages BOP funds at an early childhood institution in Makassar City, South Sulawesi, selected through criterion purposive sampling to ensure depth and richness of lived experience.Results: Findings reveal that the informant interprets the BOP fund as a trust (amanah) that must be managed transparently, responsibly, and in the best interest of learners. The informant navigates administrative burdens, disbursement delays, and multidimensional accountability demands, while sustaining practice through peer learning, disciplined recording, participatory planning, and proactive coping strategies. Conclusions: BOP fund management is not merely an administrative and compliance-driven process but is fundamentally a moral undertaking anchored in trusteeship, integrity, and dedication to community welfare, extending accountability beyond procedural compliance toward substantive, felt outcomes for children.Limitations: This study was conducted at a single early childhood institution with a limited number of informants, therefore the findings are contextual and not generalizable. Contributions: This research enriches public sector accountability scholarship through a phenomenological lens and provides practical guidance for improving BOP fund management.